2021
DOI: 10.31933/dijdbm.v2i3.834
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Consumer Value and Purchase Decisions: Analysis of Product Quality, Location, and Promotion

Abstract: Literature review is useful as a first step to initiating a study. Before determining the title, it's a good idea to prepare supporting articles for research, including previous research or as relevant research. Relevant and theory-reinforced articles are needed to look at the relationship between variables and build hypotheses. This article discusses variables that affect consumer value and consumer decisions to make decisions. The variables of product quality, location and promotion became the variables with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(39 reference statements)
1
7
0
1
Order By: Relevance
“…Previous research claims that epromotion positively and significantly impacts perceived value (Hanaysha, 2018;Septiano & Sari, 2021). Based on the findings of this study, the following hypothesis was developed:…”
Section: Relationship Between E-promotion and Perceived Valuementioning
confidence: 84%
“…Previous research claims that epromotion positively and significantly impacts perceived value (Hanaysha, 2018;Septiano & Sari, 2021). Based on the findings of this study, the following hypothesis was developed:…”
Section: Relationship Between E-promotion and Perceived Valuementioning
confidence: 84%
“…Thus, business actors agree that a product labeled halal has an influence on product sales (Helmi et al, 2019). Other research explains that a direct relationship with customer value has a significant positive impact on Victor Pascalis Gazali , Fahrul Riza purchasing decisions (Asyhari & Yuwalliatin, 2022;Septiano & Sari, 2021). Other research explains that the halalness of a product is not limited to the ingredients contained in it but also the Islamic values and cleanliness in it (Pratiwi et al, 2022;Wibowo & Mandusari, 2018), proposed hypothesis: H1: Halal Awareness has a positive and significant effect on Halal Certification.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Purchase Decision is defined as the process of selecting two or more alternative options starting from searching, evaluating product searches until consumers choose one of these options (Sandria et al, 2022). Products that are Halal certified will be directly proportional to high halal awareness, and halal awareness itself will influence decisions in purchasing halal food (Setyaningsih & Marwansyah, 2019;Efendi, 2020;Fathoni et al, 2023), while other studies have concluded that there is a significant positive direct relationship between customer value and purchasing decisions (Asyhari & Yuwalliatin, 2022;Rahman, 2020;Septiano & Sari, 2021)…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Keputusan pembelian dalam penelitian ini ialah sebuah proses mengambil putusan dalam membeli produk iPhone dan penjual akan menjalankan strategi promosi agar konsumen memutuskan untuk membeli produknya. Indikator keputusan pembelian menurut Septiano & Sari (2021), dibagi menjadi empat: kemantapan pada iPhone yakni Kualitas iPhone membuat konsumen merasa puas setelah melakukan keputuskan pembelian produk iPhone; kebiasaan membeli iPhone yakni pengulangan secara kontinu untuk membeli iPhone, pelanggan membeli produk berdasarkan kebiasaan, tidak berdasarkan loyalitas terhadap merek dan konsumen punya produk berulang kali tidak karena merek produk, tetapi karena konsumen akrab dengan produk dan terbiasa mencari informasi mengenai produk tersebut; memberikan rekomendasi pada orang lain yakni mengajak untuk membeli atau menyarankan produk iPhone kepada seseorang atau lebih bahwa produk tersebut dapat dipercaya; niat melakukan pembelian ulang yakni individu yang melakukan pembelian produk iPhone dan memutuskan untuk membeli lagi produk yang sama karena minat konsumen dalam membeli suatu produk dilihat dari pengalaman pembelian yang sudah dilakukan di masa lalu.…”
Section: Metode Penelitianunclassified